Dampak Perubahan Iklim dan Aktivitas Manusia terhadap Kerusakan Ekosistem Terumbu Karang dan Biota Laut di Sekitarnya - Dewi, Kadek Vicky Cintya; Pradesti, Rahmadiva; Nurlaela, Siti; Murnisari, Yunita; Suryanda, Ade; Aulya, Nailul Rahmi (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2023)
Coral reefs are ecosystems that have a diversity of biota in them. The main causes of damage to coral reefs are natural and human factors. This research was conducted from October to December 2022 in Jakarta. The purpose of this study was to determine the impact of climate change and human activities on damage to coral reef ecosystems and the surrounding marine biota. The method used is a literature study by collecting data and information from various research sources. The result is the influence of human activities and climate change on the destruction of coral reef ecosystems and marine and surrounding biota. There are significant impacts resulting from climate change and human activities on coral reefs and the surrounding marine biota, such as sea level rise, coral reef bleaching, and damage due to physical impacts.